Cognition, intelligence, and achievement a tribute to J.P. Das - Papadopoulos, Timothy C.; Parrila, Rauno K. 1961-; Kirby, John R. (Academic Press, 2015)
Cognition, Intelligence, and Achievement is motivated by the work of the renowned Professor J. P. Das on the PASS (Planning, Attention, Simultaneous and Successive Processing) theory of intelligence and CAS measures (Cognitive Assessment System) of cognitive processes. This book reviews current research using this and other frameworks in understanding the relationships among cognition, intelligence, and achievement. The assessment and diagnosis of learning disabilities, mental retardation, and ADHD are addressed, and the interrelationships among cognition, culture, neuropsychology, academic achievement, instruction, and remediation are examined. No other book has presented such an integrated view across these domains, from such a diverse array of internationally known and respected experts from psychology, education, and neuroscience.--Provided by publisher.